Analyzing chemical composition of buckwheat groat of different buckwheat varieties - Дубініна, Антоніна Анатоліївна; Попова, Тетяна Миколаївна; Ленерт, Світлана Олександрівна (Eastern-European Journal of Enterprise Technologies, 2014)
This paper presents the research results and the comparative analysis of the chemical composition of buckwheat groat of different buckwheat varieties. Due to the significant expansion of the range of the buckwheat cultivation all over the world, it was interesting to determine the content of specific nutrients in buckwheat groat of different buckwheat varieties, the most promising for cultivation in the forest-steppe zone. The following varieties of buckwheat, grown in the fields of the V.Ya. Yuryev Institute of Plant Industry of NAAS: Ukrainka, Yaroslavna, Kvitnik, Kosmeya, Duimovochka, Dozhdik were selected for the research. The varietes were differed by the morphological characteristics, economic and biological characteristics, origin and genetic basis. It was experimentally confirmed that the chemical composition of buckwheat groat significantly varies depending on the buckwheat variety. The most significant differences were observed in the number of nutrients by the content of protein and fiber. It was found that the high nutrient and the most balanced by the most chemical composition indexes was buckwheat groat of the buckwheat varieties of “Kosmeya”, “Kvitnik”, “Ukrainka”. These sorts can be considered as the most promising and can be regarded as plant raw materials for producing functional products and health food.